Le hasard et la nécessité. Le jeu de l’oie comme moyen d’éduquer au risque radioactif dans les années soixante - Aurélien Portelli (Images du Travail, Travail des Images)
In 1959, the Radiation Protection Service (SPR) at the Marcoule nuclear center developed a program to educate workers and the public about radioactive risk. The implementation of this program benefited from the artistic talents of Jacques Castan, a drawer at the SPR, who produced posters, brochures, a mural, a comic strip, and a game of goose entitled "Le noble jeu des lois de la radio-protection". This article proposes to study this board game, a mediating object between workers and their families, by showing its educational contribution in the era of the nuclear industry pioneers. Through playful practice, Castan’s version of the game leads the player to contemplate the rules of radiation protection, while at the same time becoming actively involved in the educational process intended for him. At the same time, the game helps to allay fears about radioactivity and to make working in a nuclear environment more commonplace. The images drawn in the boxes show that radiation protection owes nothing to chance, unlike the player’s progress, which depends solely on the result of his dice roll. Castan’s game thus invites workers and the public to believe in the effectiveness of the preventive means deployed by the SPR, an imaginary meaning that is crucial to the service because it forms the basis of the entire radiation protection structure.